The dynamics of the high-speed abilities of young players 12, 13, 14 years old - Vladimir Perevoznyk (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to determine the dynamics of the high-speed abilities of young players. Materials and Methods: the change in performance of speed players at women's 30 meters run, using both specific and non-specific methods. In the training process of players 12-14 years to use specific tools, as well as holding athletic activities for the development of speed. The literature analyzed for the development of young players quickness, educational testing, methods of mathematical statistics. Results: the dynamics of development of physical skill of speed for young players using specific and non-specific methods. Conclusions: the use of the training process in microcycle preparatory period of athletics orientation training gives a positive result in the development of the physical speed quality.